Analisis Pertumbuhan Tanaman Jagung Hibrida sebagai Pakan Ternak di Desa Olora Kota Gunungsitoli - Tri Susanti Rahmadhani Nasution; Linda Hepy Nazara; Ajaib Margaretha Harefa; Veniman Gulo; Beril Fernando Zendrato; Weldimen Waruwu; Natalia Kritiani Lase (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
This study aims to analyze the growth of hybrid maize as animal feed in Olora Village, to address the growing need for animal feed amidst limited traditional feed sources. Hybrid maize was chosen for its superior nutritional content and higher yield potential compared to local varieties. A descriptive qualitative method was used, with data collected through field observations and interviews with maize farmers. The results show that hybrid maize in Olora Village shows strong growth with high yield potential. However, challenges such as pest attacks and fertilizer shortages have been identified. Integrated pest and disease management, as well as improved soil fertility, were recommended as strategies to address these issues. This study highlights the potential of hybrid maize as a viable alternative to animal feed and provides practical recommendations to improve its cultivation.